(3GdMRH GdcHjQs - (3Ydj Hf YHO Gddg Hf YHO GdLHGQ Hf jhSa GHf gQeR GdTGPdj GdeZQHj, CHh GdMSf,J (B656 (3g` s
(3ChdgG (B:s
(3CYhP HGddg GdSejY GdYdje ef GdTjWGf GdQLje HSe Gddg GdQMef GdQMje hEPG LGAc GdPjf jhefhf HBjGJfG abd SdGe Ydjce cJH QHce Ydi faSg GdQMeI s
(3BNQgG (B:s
(3hbd QH GZaQ hGQMe hGfJ NjQ GdQGMejf agh GdMi dG Edg EdG gh aGYOYhg eNdUjf dg GdOjf GdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdSGOSs
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B662s
(3eUOQ GbJfGA GdCUd (B:s
(3ShQjG (B(9321) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs